Bitbow Enables Highly Efficient Neuronal Lineage Tracing and Morphology Reconstruction in Single Drosophila Brains - Li, Ye; Walker, Logan A.; Zhao, Yimeng; Edwards, Erica M.; Michki, Nigel S.; Cheng, Hon Pong Jimmy; Ghazzi, Marya; Chen, Tiffany Y.; Chen, Maggie; Roossien, Douglas H.; Cai, Dawen (Frontiers in Neural Circuits, 2021)
Identifying the cellular origins and mapping the dendritic and axonal arbors of neurons have been century old quests to understand the heterogeneity among these brain cells. Current Brainbow based transgenic animals take the advantage of multispectral labeling to differentiate neighboring cells or lineages, however, their applications are limited by the color capacity. To improve the analysis throughput, we designed Bitbow, a digital format of Brainbow which exponentially expands the color palette to provide tens of thousands of spectrally resolved unique labels. We generated transgenic Bitbow Drosophila lines, established statistical tools, and streamlined sample preparation, image processing, and data analysis pipelines to allow conveniently mapping neural lineages, studying neuronal morphology and revealing neural network patterns with unprecedented speed, scale, and resolution.